Urbanisation Levels and Socio-Economic Correlates of Asian Muslim Countries. - Dutt, Ashok K. et.al (2008)
Asian countries, with a majority of Muslim population, demonstrate specific characteristics in their urban association with socio-economic variables. A case study of Saudi Arabia, Pakistan, Bangladesh and Indonesia shows that early origin of Islam and ancient city-based civilisation have no direct effect on current urbanisation. It is the economic boom, mainly resulting from oil extraction, which has worked as an engine of modernisation and increase in urban population. Pearson correlation, regression analysis and factor analysis not only complement each other but confirm the explanatory socio-economic correlates. A confident conclusion is that it is the increase of wealth that is largely responsible for raising urban levels of Asian Muslim countries.